Innovation System in Agricultural Downstream Supply Chain: A Systematic Literature Review and Future Challenges - Noveria Sjafrina; Marimin Marimin; Faqih Udin; Elisa Anggraeni (International Journal of Supply Chain Management, 2020)
Since global issues (i.e. disruption technology and sustainability) attracted the attention of agricultural system researchers and company, innovation system plays a significant role in the development of agricultural downstream supply chain, in order to make agriculture business sustain. Hence, researches in innovation system for agricultural downstream supply chain are very important in dealing with these challenges. The aim of this paper is to investigate the current state of researches, current development, gaps and provide guidance for future research of innovation system and agricultural downstream supply chain research field. A systematic literature review was conducted to achieve the research goal. After applying some relevant keywords filter and including some relevant papers published in the field, 110 papers addressing the innovation system in agricultural downstream supply chain are identified for review analysis. Afterwards, the selected papers are categorized according to the topic and keyword considered. From this classification, current research and gaps in the existing literature are analysed and derived to make a current research state of innovation system (IS) and its development-relationship with agricultural downstream supply chain (ADSC) research area. Then, Potential areas guidance for future research are suggested for the development of technology diffusion and stakeholder interaction through innovation system, in order to make ADSC facing technology disruption